2020
DOI: 10.1093/ije/dyaa140
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictors of hospitalization and death in the first 11 122 cases with a positive RT-PCR test for SARS-CoV-2 in Denmark: a nationwide cohort

Abstract: Background Population-level knowledge on individuals at high risk of severe and fatal coronavirus disease 2019 (COVID-19) is urgently needed to inform targeted protection strategies in the general population. Methods We examined characteristics and predictors of hospitalization and death in a nationwide cohort of all Danish individuals tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from 27 February 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
272
7
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(320 citation statements)
references
References 18 publications
32
272
7
9
Order By: Relevance
“…Previous studies have reported widely varying overall COVID-19 mortality rates, e.g., 1.4% among 1,099 cases in Wuhan, China (14), and 7.2% among 22,512 in Italy (15). In our study, the overall 30-day COVID-19 mortality was 6.1% and males over 60 years of age were overrepresented, which is well in line with previous data from COVID-19 patients from Denmark (16). Importantly, mortality rates are very different among in- and outpatients.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported widely varying overall COVID-19 mortality rates, e.g., 1.4% among 1,099 cases in Wuhan, China (14), and 7.2% among 22,512 in Italy (15). In our study, the overall 30-day COVID-19 mortality was 6.1% and males over 60 years of age were overrepresented, which is well in line with previous data from COVID-19 patients from Denmark (16). Importantly, mortality rates are very different among in- and outpatients.…”
Section: Discussionsupporting
confidence: 91%
“…The evidence for an association between air pollution and mortality starting at slightly lower nitrogen dioxide levels in the present study could stem from an association between air pollution and severe COVID-19, mediated by a high chronic disease prevalence existing already at relatively low levels of nitrogen dioxide exposure. Evidence is clear that a higher prevalence of comorbidities may lead to a more clinically severe form of COVID-19 and to a higher mortality from the disease (Onder et al, 2020;Reilev et al, 2020;Ssentongo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…21 Despite these strengths, the study had several limitations. The threshold for SARS-CoV-2 20 Importantly, our results did not change after restriction to patients tested after the policy guidelines changed and the country was locked down on 13 March 2020. Any bias should be minimal as use of ACE-I/ ARB was not expected to influence the threshold for testing, which followed national guidelines.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 60%
“…The unique personal identification number assigned at birth or on immigration allows individual-level linkage of data and complete follow-up. 19 As previously described, 20 data on all individuals tested for SARS-CoV-2 RNA by reverse transcriptase PCR (RT-PCR) were obtained from the Danish Microbiology Database 21 and linked to regularly updated data from the Danish National Patient Registry, 22 the Civil Registration System, 23 the National Prescription Database 24 and the Danish Register of Causes of Deaths. 25…”
Section: Design and Settingmentioning
confidence: 99%